2019
DOI: 10.3390/mi10030202
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of AlN Intermediate Layer on the Structural and Chemical Properties of SiC Thin Films Produced by High-Power Impulse Magnetron Sputtering

Abstract: Many strategies have been developed for the synthesis of silicon carbide (SiC) thin films on silicon (Si) substrates by plasma-based deposition techniques, especially plasma enhanced chemical vapor deposition (PECVD) and magnetron sputtering, due to the importance of these materials for microelectronics and related fields. A drawback is the large lattice mismatch between SiC and Si. The insertion of an aluminum nitride (AlN) intermediate layer between them has been shown useful to overcome this problem. Herein… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…A nanocrystalline structure (but with different phases) was recently reported by Galvão et al [ 19 ] for SiC films deposited by HiPIMS at ambient temperature. The XRD results reported in this paper are more consistent with those reported by Craciun [ 30 ] and Keffous [ 31 ].…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…A nanocrystalline structure (but with different phases) was recently reported by Galvão et al [ 19 ] for SiC films deposited by HiPIMS at ambient temperature. The XRD results reported in this paper are more consistent with those reported by Craciun [ 30 ] and Keffous [ 31 ].…”
Section: Resultsmentioning
confidence: 63%
“…As compared to the DCMS technique, due to a higher ion-to-neutral flux ratio and higher kinetic energy of sputtered particles, the coatings deposited by HiPIMS present higher density and demonstrate better adhesion on the substrate. Recently, Galvão et al have shown that HiPIMS can be used to fabricate nanocrystalline SiC thin films without heating or biasing the Si substrate by making deposits on top of AlN interlayers [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…As early as 1983, Shigehiro et al proposed a reproducible process for producing single-crystal SiC with an intermediate buffer layer of sputtered SiC [30]. Furthermore, Nierlly et al reported that the lattice mismatch problem between SiC and Si could be overcome by using an aluminum nitride (AlN) intermediate layer [31]. Therefore, it is desirable for SiC thin films to be grown on Si-substrates.…”
Section: Process Flowmentioning
confidence: 99%
“…These wurtzite nitrides are generally deposited on sapphire, Si, SiC, and diamond substrates with heteroepitaxial growth by several methods including DC-RF sputter deposition, metal–organic chemical vapor deposition (MOCVD), molecular-beam epitaxy (MBE), pulsed laser deposition (PLD), and advanced methods such as atomic layer deposition (ALD) and electron beam physical vapor deposition. The polycrystalline wurtzite nitride growth results in the formation of both metal (e.g., Al, Ga, and Sc) polar and N polar grains that generate inversion domain boundaries (IDBs) between the grains of different polarities . The IDBs were examined structurally to find reliable atomic arrangements .…”
Section: Introductionmentioning
confidence: 99%